The association between Hba1c levels, olfactory memory and cognition in normal, pre-diabetic and diabetic persons - (:unkn) unknown (Bentham Science Publishers, 2020)
Background and Aim: Recent data have shown that olfactory dysfunction is strongly related to Alzheimer’s Disease (AD) that is often preceded by olfactory deficits suggesting that olfactory dysfunction might represent an early indicator of future cognitive in prediabetes. Methods: We have applied to a group of normal (n=15), prediabetic (n=16) and type 2 diabetic outpatients (n=15) olfactory testing, 1.5-T MRI scanner and detailed cognitive evaluation including the standard Mini-Mental State Examination (MMSE) form, Short Blessed Test (SBT), Letter Fluency Test (LFT) and the category fluency test with animal, Fruit and Vegetable Naming (CFT). Results: We have shown that Odour Threshold (OT), Discrimination (OD), and Identification (OI) scores and most cognitive test results were significantly different in the prediabetes and diabetes group compared to those in the control group. OD and OT were significantly different between the prediabetes and diabetes group, although the cognitive test results were only significantly different in the prediabetes and diabetes group compared to those in the control group. In evaluating the association between OI, OT, OD scores and specific cognitive tests, we have found, that impaired olfactory identification was the only parameter that correlated significantly with the SBT both in the pre-diabetes and diabetes group. Although spot glucose values were only correlated with OT, HbA1c levels were correlated with OT, OD, and OI, as well as results of the letter fluency test suggesting that HbA1c levels rather than the spot glucose values play a critical role in specific cognitive dysfunction. Conclusion: To the best of our knowledge, this is the first prospective study to demonstrate a strong association between olfactory dysfunction and specific memory impairment in a population with prediabetes and diabetes suggesting that impaired olfactory identification might play an important role as a specific predictor of memory decline. © 2020 Bentham Science Publishers.
Keywords: Cognition; Diabetes; Memory dysfunction; Olfaction; Olfactory memory; Prediabetes